2022
DOI: 10.1093/isq/sqac015
|View full text |Cite
|
Sign up to set email alerts
|

Resisting Lockdown: The Influence of COVID-19 Restrictions on Social Unrest

Abstract: Responding to the COVID-19 pandemic has created unprecedented social and political challenges. Mitigation strategies often disrupt the daily lives of citizens and constrain rights and privileges. Policies intended to contain disease spread have provoked resentment, resistance, and backlash. We examine the extent to which specific COVID-19 policy responses influence the frequency of civil unrest. Combining insights from both grievance and opportunity models of dissent, we contend that pandemic-response policies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Several recent studies have examined the correlates of public unrest during the COVID-19 pandemic or sought to identify the conditions that gave rise to organized opposition to restrictions. These studies highlight the role of opportunity structures in shaping anti-lockdown mobilization: protests frequency was negatively correlated with COVID-19 infection rates, negatively related to restrictions on domestic transportation and movement, and positively correlated with pre-existing state respect for civil liberties (Neumeyer, Pfaff, and Plümper, 2023; Plümper, Neumeyer, and Pfaff, 2021; Wood et al, 2022). Moreover, they suggest that grievances and general attitudes toward authorities influenced protest location and intensity.…”
Section: Covid-19 Pandemic Mitigation Strategies and Popular Unrestmentioning
confidence: 90%
See 3 more Smart Citations
“…Several recent studies have examined the correlates of public unrest during the COVID-19 pandemic or sought to identify the conditions that gave rise to organized opposition to restrictions. These studies highlight the role of opportunity structures in shaping anti-lockdown mobilization: protests frequency was negatively correlated with COVID-19 infection rates, negatively related to restrictions on domestic transportation and movement, and positively correlated with pre-existing state respect for civil liberties (Neumeyer, Pfaff, and Plümper, 2023; Plümper, Neumeyer, and Pfaff, 2021; Wood et al, 2022). Moreover, they suggest that grievances and general attitudes toward authorities influenced protest location and intensity.…”
Section: Covid-19 Pandemic Mitigation Strategies and Popular Unrestmentioning
confidence: 90%
“…Moreover, they suggest that grievances and general attitudes toward authorities influenced protest location and intensity. For example, protests were more common where restrictions were more severe, more costly, or more disruptive to the everyday lives of citizens (Kriesi and Oana, 2022; Plümper, Neumeyer, and Pfaff, 2021; Wood et al, 2022) and were less common where citizens reported higher levels of confidence and trust in authorities (Neumeyer, Pfaff, and Plümper, 2023).…”
Section: Covid-19 Pandemic Mitigation Strategies and Popular Unrestmentioning
confidence: 99%
See 2 more Smart Citations
“…This transition may act as a deep lever of change that allows for better multi-hazard management, which is of crucial importance given the fact that the COVID-19 management practices have significantly influenced and are influenced by risk mitigation practices that were designed prior to this global outbreak. The COVID-19 pandemic has caused severe and prolonged health problems (Poudel et al 2021 ; Kanne et al 2022 ; Vyas et al 2022 ), the overburdening of medical systems (Bigoni et al 2022 ; Chanda-Kapata et al 2022 ; Chemali et al 2022 ), social tensions (Donoso et al 2022 ; Fahs and Swank 2022 ; Rohlinger and Meyer 2022 ; Wood et al 2022 ), and economic disruptions (Choi et al 2022 ; Khetan et al 2022 ), increasing the vulnerability of human communities to other natural hazards and depleting their capacity to cope with hazards. On the other hand, certain hazard management practices hindered the implementation of COVID-19 preventive protocols (e.g., social distancing is difficult to maintain during evacuation procedures or in emergency shelters), damaged the medical and/or transport infrastructure, and negatively affected pandemic relief workers and volunteers (Shultz et al 2020 ; Ashraf 2021 ).…”
Section: Introductionmentioning
confidence: 99%